Macular microcirculation and macular oedema in branch retinal vein occlusion. Issue 5 (10th February 2009) - Noma, H; Funatsu, H; Sakata, K; Harino, S; Nagaoka, T; Mimura, T; Sone, T; Hori, S
Abstract : Background/aims: The relationship between the blood-flow velocity in the perifoveal capillaries and macular oedema was investigated in patients with branch retinal vein occlusion (BRVO). Methods: This study compared 18 patients with BRVO and 16 healthy volunteers. Perifoveal capillary blood-flow velocity was measured on fluorescein angiograms with a scanning laser ophthalmoscope by the tracing method. Retinal thickness at the central fovea was measured by optical coherence tomography. Then, the relation between perifoveal capillary blood-flow velocity and retinal thickness at the central fovea was investigated. Results: Perifoveal capillary blood-flow velocity was significantly lower in the patients with BRVO (1.08 (SD 0.28) mm/s) than in the healthy volunteers (1.49 (0.11) mm/s) (p<0.0001). Capillary blood-flow velocity showed a negative correlation with the retinal thickness at the central fovea in the two groups (r = −0.8426, p<0.0001). Multivariate linear regression analysis with stepwise variable selection confirmed that capillary blood-flow velocity was an independent determinant of the retinal thickness at the central fovea (p<0.001). Conclusion: A reduction in perifoveal capillary blood-flow velocity may be involved in the development of macular oedema in patients with BRVO.